2002
DOI: 10.1002/rcm.771
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic investigation of the interaction between bisquaternary antimicrobial agents and phospholipids by liquid secondary ion mass spectrometry and differential scanning calorimetry

Abstract: Mechanisms of interaction between the antimicrobial drugs decamethoxinum and aethonium, which are based on bisquaternary ammonium compounds, and a phospholipid component of biological membranes, dipalmitoylphosphatidylcholine, were studied by means of liquid secondary ion mass spectrometry (LSIMS) and differential scanning calorimetry (DSC). Supramolecular complexes of the drugs with this phospholipid were recorded under secondary ion mass spectrometric conditions. The dependence of the structures of these com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 21 publications
3
21
0
8
Order By: Relevance
“…When comparing ion generation and energy deposition with different soft ionization techniques, it is of interest to compare mass spectra of decamethoxinum obtained by ESI at different CV values with those obtained in earlier studies with other desorption techniques 11–16. Such a comparison shows that the mass spectra obtained at different CV values under ESI never coincide completely with those obtained with FD, FAB and liquid SIMS.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…When comparing ion generation and energy deposition with different soft ionization techniques, it is of interest to compare mass spectra of decamethoxinum obtained by ESI at different CV values with those obtained in earlier studies with other desorption techniques 11–16. Such a comparison shows that the mass spectra obtained at different CV values under ESI never coincide completely with those obtained with FD, FAB and liquid SIMS.…”
Section: Resultsmentioning
confidence: 97%
“…Quaternary ammonium salts are popular test compounds that have been studied by various soft mass spectrometric techniques,1–10 since the presence of fixed ‘preformed’ charges in their organic cations facilitates investigations on the fundamentals of ion generation and on fragmentation pathways. In our previous studies11–17 we selected the bisquaternary ammonium compound decamethoxinum as a structure and energy probe for soft ionization methods, because it demonstrated a strong dependence of the types of ions recorded in the mass spectra on the mass spectrometric technique and experimental conditions applied. Data on the fragmentation of decamethoxinum obtained with liquid secondary ion mass spectrometry (SIMS)11 and matrix‐assisted laser desorption/ionization (MALDI)12 techniques were reported.…”
mentioning
confidence: 99%
“…It was decided to compare positive and negative ion LSIMS spectra of cationic and anionic surfactants and their binary mixtures. We selected two bisquaternary ammonium salts, decamethoxinum and aethonium, well studied in our previous works,18–21 as cationic surfactants and the widely used sodium dodecyl sulfate (SDS) as an anionic surfactant. The data obtained were interpreted by applying the notions of surface and colloid chemistry concerning the interfacial EDL.…”
mentioning
confidence: 99%
“…In our earlier mass spectrometric study on molecular mechanisms of action of antimicrobial drugs based on bisquaternary ammonium compounds,31 we studied decamethoxinum which has shown strong dependence of the types of several precursor ions produced and of their fragmentation patterns on the desorption/ionization technique applied and on the variation of some experimental parameters within one technique 32. In this connection we have suggested that a more detailed study of this particular compound can contribute to clarification of the mechanism of the fragmentation of bisquaternary compounds and throw light on the question of the stability of the organic dications in the gas phase.…”
mentioning
confidence: 99%